Tajemnica polskiego zlota - Nowakowski, Krzysztof; Nowakowski, Krzysztof (Warszawa : Oficyna Wydawnicza RYTM, 1991)
Novel about a real incident in which Gold bullion from the Bank of Poland was shipped out of the country in 1939 and ended up in the French Sudan.
Translation of: Polish gold.
Keywords: Gold -- Fiction; Poland -- History -- 1918-1945 -- Fiction